The Role of Superior Support Mediated by Organisation Commitment, Work Environment, and Job Enrichment on OCB - Prasmawati, Rita; Raharjo, Pamuji Gesang; Efendi, Efendi (Technium Social Sciences Journal, 2023)
This research aims to identify the determinant factors that foster OCB in the hospitality business where the variables are superior support, organizational commitment, work environment, and job enrichment. The population is employees of the Jababeka Group Hospitality. Accidental sampling is a technique used to conduct surveys. A total of 202 people were willing to fill out the questionnaire. The relationship between the variables is analyzed with the help of structural equation modeling (SEM). Smartpls is used to help this process. This research concludes that organizational commitment and job enrichment contribute both directly and significantly to incentivizing OCB to grow. Through the mediation of organizational commitment and work environment, as well as job enrichment, this mediation also contributes indirectly and quite significantly where the role of superior support becomes stronger which encourages OCB. On the other hand, the work environment is not able to provide a direct and significant influence on OCB, it needs to be mediated by superior support. Implications are discussed from this finding for researchers and practitioners, if superiors play an active role in supporting the needs to bend and inspiring their team, then this can foster OCB behavior that has an impact on the success of an organization.